The ordeal of the longhouse : the peoples of the Iroquois League in the era of European colonization - Richter, Daniel K. (Published for the Omohundro Institute of Early American History and Culture, Williamsburg, Virginia., 1992)
"Richter examines a wide range of primary documents to survey the responses of the peoples of the Iroquois League--the Mohawks, Oneidas, Onondagas, Cayugas, Senecas, and Tuscaroras--to the challenges of the European colonialization of North America. He demonstrates that by the early eighteenth century a series of creative adaptations in politics and diplomacy allowed the peoples of the Longhouse to preserve their cultural autonomy in a land now dominated by foreign powers."--Amazon.com.